Pengaruh Motivasi Berprestasi Terhadap Hasil Belajar Ekonomi dengan Iklim Kelas Sebagai Variabel Moderator - Khairil Insan Bintang (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2023)
This research is motivated by the learning outcomes of students in economics subjects at Senior High School in Bandung City which have not been optimal seen through the average value of the Final Semester Assessment which did not reach the Minimum Completeness Criteria. This study aims to determine the effect of achievement motivation and class climate on economics learning outcomes. The research method used is an explanatory survey. The population consisted of class X Social Studies students at Senior High School in Bandung City Region A with a sample of 259 students who were determined using a random sampling technique. The data analysis technique used is regression analysis with Moderated Regression Analysis (MRA). The results showed that: (i) achievement motivation had a significant positive effect on student learning outcomes (ii) class climate had a significant positive effect on student learning outcomes (iii) class climate moderated the effect of achievement motivation on student learning outcomes.